SmEIL1 transcription factor inhibits tanshinone accumulation in response to ethylene signaling in Salvia miltiorrhiza - Li, Xiujuan; Xu, Man; Zhou, Ke; Hao, Siyu; Li, Liqin; Wang, Leran; Zhou, Wei; Kai, Guoyin (Frontiers in Plant Science, 2024)
Among the bioactive compounds, lipid-soluble tanshinone is present in Salvia miltiorrhiza, a medicinal plant species. While it is known that ethephon has the ability to inhibit the tanshinones biosynthesis in the S. miltiorrhiza hairy root, however the underlying regulatory mechanism remains obscure. In this study, using the transcriptome dataset of the S. miltiorrhiza hairy root induced by ethephon, an ethylene-responsive transcriptional factor EIN3-like 1 (SmEIL1) was identified. The SmEIL1 protein was found to be localized in the nuclei, and confirmed by the transient transformation observed in tobacco leaves. The overexpression of SmEIL1 was able to inhibit the tanshinones accumulation to a large degree, as well as down-regulate tanshinones biosynthetic genes including SmGGPPS1, SmHMGR1, SmHMGS1, SmCPS1, SmKSL1 and SmCYP76AH1. These are well recognized participants in the tanshinones biosynthesis pathway. Further investigation on the SmEIL1 was observed to inhibit the transcription of the CPS1 gene by the Dual-Luciferase (Dual-LUC) and yeast one-hybrid (Y1H) assays. The data in this work will be of value regarding the involvement of EILs in regulating the biosynthesis of tanshinones and lay the foundation for the metabolic engineering of bioactive ingredients in S. miltiorrhiza.